Paciente masculino de 80 años diagnosticado con enfermedad pulmonar obstructiva crónica. - Ortega Rodríguez, Karla Elizeth (2021)
Evidence is made of a clinical case study in an 80-year-old patient with a clinical picture characterized by respiratory distress, progressive hypotonia, cough of several days of evolution, was evaluated and admitted to the hospital in which complementary examinations are performed and is diagnosed with chronic obstructive pulmonary disease. Chronic obstructive pulmonary disease is defined as a pathophysiological process, which is characterized by limiting the flow of air to the lungs, in most cases progressively, its symptomatic picture of chronic obstructive pulmonary disease is usually accompanied by persistent respiratory symptoms that limit the exchange of gases in the pulmonary alveoli, one of the most relevant etiologies is the consumption of tobacco and exposure to gases such as carbon monoxide which are found in the burning of different types of materials of daily use in people's lives. The World Health Organization classifies it as one of the most frequent respiratory pathologies in the world with a high mortality rate which reached the third place in the number of deaths in 2020, it is a disease of relevance for the public health system at the national level because it generates great need in the socio-economic, medical, and social. The objective of the study is to recognize the clinical picture in the patient to provide an optimal treatment that guarantees their survival.